WORK PERFORMANCE IN ACCOUNTANT PRIVATE COMPANIES FORMED IN MANABI UNIVERSITIES - Bermúdez Tacunga, Rafael (2015)
In this article we made an analysis of the professional training the accountants received in universities from Manabi, they maintain working activities with compa-nies operating within the same province, since there is usually an obvious contradiction between the higher education offered by universities and the requirements an enterprise needs of a hired professional regarding the knowledge, skills and values that they have for the exercise of their functions. The research was ex-ploratory and descriptive; the methodology adopted in the research for the collection of information via email, was made by developing a questionnaire with closed questions about the training in universities and their applicability in the functions performed; a sample of 40 accountants were handed the instrument to determine the level of satisfaction with the training received in higher education institutions. Among the most relevant results and of which the conclusions in the article were derived, we highlight certain aspects of dissatisfaction shown by respondents regarding the use of technology in their university training.